Rapid Synthesis: Using Non-Medical Home Services to Support Older Adults - Waddell, K; Wilson, MG (My University, 2016)
An assessment of what is known about the non-medical home services that support older adults. The rapid synthesis was conducted to address a question posed by a health system policymaker or stakeholder to the McMaster Health Forum's Rapid Response program.
Keywords: using; non-medical; home; services; support; older; adults